Risky earnings, taxation and entrepreneurial choice: a microeconometric model for Germany - Frank M. Fossen (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Which role do individual income prospects play in the decision to be an entrepreneur rather than an employee? In a model of occupational choice, higher expected after-tax earnings attract people to self-employment, while more risky net earnings deter risk-averse individuals. In this paper I analyse the expected value and variance of income in self-employment and dependent employment empirically, accounting for selection. Based on this analysis, structural models of self-employment entry and exit under risk are estimated, which include a standard risk aversion parameter. The model predicts that the German income tax reduction of 2000 induced smaller exit rates out of self-employment for men and smaller entry rates for women.
Keywords: J23; H24; D81; C51; 330; Entrepreneurship; Risk; Returns to Self-Employment; Taxation; Berufswahl; Unternehmer; Einkommen; Risiko; Einkommensteuer; Mikroökonometrie; Schätzung; Deutschland